(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The verbal testwhich has been described in the present material is part of the total batterywhich consists of both verbal and non-verbal tests. The verbal test ofcreativity includes four subtests namely consequences test, unusualness test,similarity test and product improvement test. The totaltime required for administering the test is 48 minutes in addition to the time necessary for giving instructions, passing out tests booklets to children and collecting them back. In thepresent investigation the Llkert’s (1932) Amethod has been followed which ismore convenient as far as administrative, economic and time facilities areconcerned. The investigator prepared 39 statements which are related toreligion. The statements of the scale have the following features: i) All the statements are related toreligion. ii) All the statements are to be markedon a live point rating scale. iii) The statements are simple, specific and clear. iv) The statements are in the form ofopinions rather than a narration of facts. Appropriateinstructions have been given in the scale.